Implementation PBL Model Assisted by E-Module Based on Refutation Text to Overcome Student Misconceptions on Dynamic Electricity Topics - Lidiya Rahmawati; Stepanus Sahala Sitompul; Ray Cinthya Habellia; Lanang Maulana Aminullah (Jurnal Penelitian Pembelajaran Fisika, 2025)
This research was conducted with the aim of addressing students' misconceptions in dynamic electricity topics through the application of the Problem Based Learning (PBL) model assisted by an e-module based on refutation text. The research design uses an experimental method, in the form of a pre-experimental design and a one-group pretest-posttest design, as well as the cluster random sampling technique. This research was conducted at SMP Negeri 2 Pontianak, with a research sample consisting of 31 ninth-grade students. The data collection instrument consisted of five items in the form of a two-tier multiple-choice test, and the results were categorized based on the combination of students' answers and justifications. The data obtained in the study were analyzed using normality tests and the Wilcoxon test, as well as effect size calculations using Cohen's formula as adopted by Glass. The research results show that the average misconception rate among students decreased from 43.2% to 14.9%, with an average misconception reduction of 28.3%, as evidenced by the Wilcoxon test results with an Asymp.Sig value of 0.000 (0.000 < 0.05), and an effect size calculation result of 3.14 (high category). This study proves that the application of the PBL model assisted by an e-module based on refutation text can overcome students' misconceptions in dynamic electricity topics with a high level of effectiveness.